2020
DOI: 10.1177/1120700020938576
|View full text |Cite
|
Sign up to set email alerts
|

How reliable is the next generation of multiplex-PCR for diagnosing prosthetic joint infection compared to the MSIS criteria? Still missing the ideal test

Abstract: Introduction: Identification of the pathogen in case of a periprosthetic joint infection (PJI) remains 1 of the greatest challenges in septic surgery. Rapid germ identification enables timely, specific, antimicrobial therapy. The first multiplex PCR (polymerase chain reaction) generation (Unyvero-i60) enables germ detection within 5 hours with a sensitivity of 78.8% and a specificity of 100%. The aim of this study is to investigate the performance of the new generation of cartridges (Unyvero-ITI) of multiplex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 27 publications
(35 reference statements)
0
17
0
2
Order By: Relevance
“…Recently, we evaluated the second-generation Unyvero ITI cartridge on joint aspirate specimens and demonstrated an improved diagnostic accuracy in comparison to routine cultures, with a sensitivity of 80% 10 . Similarly, Lausmann et al demonstrated an increased performance of the novel Unyvero ITI cartridge when analysing synovial fluid of 97 patients, with a sensitivity of 85% 28 .…”
Section: Discussionmentioning
confidence: 92%
“…Recently, we evaluated the second-generation Unyvero ITI cartridge on joint aspirate specimens and demonstrated an improved diagnostic accuracy in comparison to routine cultures, with a sensitivity of 80% 10 . Similarly, Lausmann et al demonstrated an increased performance of the novel Unyvero ITI cartridge when analysing synovial fluid of 97 patients, with a sensitivity of 85% 28 .…”
Section: Discussionmentioning
confidence: 92%
“…Synovial polymerase chain reaction studies. Overall, 20 studies described the diagnostic accuracy of synovial fluid PCR in the detection of PJi, using the msis criteria as the standard reference test, [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] with baseline characteristics of individual studies shown in table i. three studies contributed to two data points each, as these studies published data on different PCR Fig. 6 Forest plot for synovial fluid calprotectin studies.…”
Section: Resultsmentioning
confidence: 99%
“…PCR-based techniques are independent from bacterial culture and operate directly on patient samples, decreasing turn-around times to a few hours [ 15 , 16 ]. Lausmann et al (2020) tested the Unyvero ITI ® PCR cartridge on 97 patients with aseptic or septic, hip or knee revision surgery, and obtained an overall accuracy of 91.8% [ 17 ]. BioFire ® Bone and Joint Infection was evaluated by Graue et al on 1544 patient samples and the obtained overall sensitivity was 90.2% and specificity was 99.8% [ 18 ].…”
Section: Standard Of Care Diagnostic Methods For Pji Managementmentioning
confidence: 99%